Management of patients with early-stage triple-negative breast cancer following pembrolizumab-based neoadjuvant therapy: What are the evidences?. (November 2022) - Bonadio, Renata Colombo; Tarantino, Paolo; Testa, Laura; Punie, Kevin; Pernas, Sonia; Barrios, Carlos; Curigliano, Giuseppe; Tolaney, Sara M.; Barroso-Sousa, Romualdo
Highlights: Neoadjuvant pembrolizumab plus chemotherapy is a new standard of care for TNBC. For residual disease, pembrolizumab, capecitabine, and olaparib are adjuvant therapy options. We reviewed efficacy and safety data to guide adjuvant therapy selection. Combinations of pembrolizumab plus capecitabine or olaparib seem safe. Combination strategies of adjuvant therapy lacks on supportive efficacy data. Abstract: New therapy options have changed the treatment landscape of early-stage triple-negative breast cancer (TNBC) in recent years. Most patients are candidates for neoadjuvant chemotherapy, which helps to downstage the tumor and tailor adjuvant systemic therapy based on pathologic response. Capecitabine, pembrolizumab, and olaparib have been incorporated into the armamentarium of adjuvant treatment for selected patients. The KEYNOTE-522 trial, that demonstrated the benefit of pembrolizumab, given in addition to neoadjuvant chemotherapy and adjuvantly after surgery, represented a paradigm shift for early-stage TNBC treatment. Pembrolizumab was continued in the adjuvant setting irrespective of response to neoadjuvant therapy, and other adjuvant therapies were not administered in the trial. Many questions were then raised on the selection of adjuvant therapy regimens for patients with residual disease (RD). Prior to the routine use of immune-checkpoint inhibitors (ICI), the value of adjuvant capecitabine for patients with RD after neoadjuvant polychemotherapy was demonstrated. Given the poor prognosis of some patients with RD after neoadjuvant chemo-immunotherapy, while the survival advantage of adding capecitabine during the adjuvant phase of pembrolizumab is unknown, it does appear safe and can be considered. Regarding patients harboring germline BRCA mutations with RD after neoadjuvant ICI-containing regimens, the combination of olaparib with pembrolizumab can be an option based on existing safety data.